Pengaruh Likuiditas, Profitabilitas terhadap Nilai Perusahaan Industri Sektor Semen di Indeks Saham Syariah Indonesia 2013 -2022 - Faidah Rizkiah Ritonga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to confirm the effect of liquidity and profitability performance on the performance of the company’s value in the cement sector company in Indonesia. The data used in this study are secondary data with panel data types that combine time series and cross section data from annual reports. The population and samples of research are sub-sector companies registered on ISSI or the Indonesian Sharia Stock Index for annual report pulished consistently for the 2013 period -2022. A number of 5 companies on the ISSI for a period of 10 years so that the number of samples used is 50 samples. The analysis method used is quantitative with panel data regression analysis. The research results show that liquidity performance has a partial influence on company value with a significance level of 0.018. Meanwhile, partial profitability performance does not have an influence of 0.6104 on company value. Meanwhile, simultaneously, the current ratio liquidity and ROA profitability variables have no effect on company value with a significance level of 0.2838.